A PRECÁRIA FISCALIZAÇÃO DAS CONDIÇÕES LABORAIS DOS VENEZUELANOS NO BRASIL PELO MINISTÉRIO PÚBLICO FEDERAL (Direito e Humanidades, 2025)
This article will address the monitoring of the forms of work of Venezuelan refugees in Brazil. Its objective will be to analyze, based on the concept of decent work, how the forms of work of Venezuelan refugees whose asylum application has been granted are carried out and their monitoring by the Federal Public Prosecutor's Office in Brazil, through the analysis of the decisions of this body.
Keywords: migrant; refuge; decent work; supervision; Federal Public Ministry